Collaborative approaches to health education: perspectives of parents and teachers on self-care and managing common health issues in UK primary schools - Samira Osman; Christine Hirsch; Zahraa Jalal; Vibhu Paudyal (BMC Health Services Research, 2024)
Abstract Background Health education in primary schools plays a critical role in equipping children with essential self-care skills, fostering health literacy, and addressing social determinants of health. This study explores the perspectives of parents and teachers on teaching self-care and managing common health issues in UK primary schools. Despite the recognized importance of health education, there is limited research on how self-care education is perceived and implemented in the primary school setting. Methods A qualitative study was conducted using semi-structured interviews with 18 participants, including 9 generalist primary teachers and 9 parents from diverse educational and socioeconomic contexts in the West Midlands, East Midlands, Northwest, and London of England. Participants were recruited via social media and professional networks, and interviews were conducted via video conferencing platforms. Data were thematically analysed using NVivo 12 to identify recurring themes related to the delivery and impact of self-care education in primary schools. Results Teachers and parents highlighted key self-care topics, including hygiene, managing common illnesses like colds and cuts, and mental well-being. There was a consensus on the importance of self-care education, but views diverged on whether the responsibility should lie primarily with schools, parents, or a collaborative approach. Teachers expressed concerns about their preparedness to teach sensitive topics, citing a lack of training and resources. Socioeconomic and religious contexts further influenced perceptions, with participants emphasising further importance of school-led self-care education for children from lower socioeconomic backgrounds. Strengths were identified in current self-care education efforts, particularly in practical lessons that empower children with age-appropriate skills. Conclusions This study highlights the critical need for comprehensive and collaborative health education in primary schools to promote health literacy and reduce health disparities. Enhancing teacher training, integrating self-care topics into the primary curriculum, and fostering stronger partnerships between schools and families are essential to improving the quality and consistency of self-care education. Policymakers should consider implementing mandatory health education training in teacher education programs and providing ongoing professional development to support teachers. By addressing these gaps, schools can play a pivotal role in preparing children for lifelong health management, reducing the burden on healthcare services, and supporting public health objectives.